Children who witness domestic violence - BOUKERZAZA , Khaoula (Journal of Human Sciences, 2023)
This stydy is about the impact or influence the kids of the couple’s violence; these kids are the witnesses of this sufferance all days. They also, live and feel the battesed mother’s feelings; they understand the silent mother’s impact; so they acquire a cousole bahaviour towards then. We are testing troubles which are developping kids witness of couples violence as being and externalized enter with a focus on aggressiveness, augnish and psychomatic troubles. Through the stydy case sustaired by TAT, project instrument of a lived conflictual and violent where emerge the story of each ease; this contribute to reveal a solid self or immature childish or soft.consequenthy a neurotic personnality or psychotic by default repressed and insatisfied inconscious fantasy.the violence cycle distrubs communication inside the couple, destroy familial ideas ( habits and costums); the role of the women is being the protectim of children beside the man uses force abuses and its domination. Between his two parents who dismissal affiction and intricates; the child witness of couple violence by default, lack of identification or imitation is in front of ignored traumatic reality or badly expressed by aggressive drive to show its existence, find ar occupation for parents by troubles apparition, runaway from home, barburate consumption, suicide in order to solve the probleme or escape the conflict.